Enhancing Intuition through Tazkiyatun Nafs: A Pathway to Preventing Unethical Conduct - Hasan Mud’is (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to comprehensively explore the multifaceted nature of Tazkiyatun Nafs as a pathway to enhance intuition and prevent unethical behavior. Through a meticulous examination of the transformative potential inherent in Tazkiyatun Nafs, this research endeavors to shed light on how this spiritual practice can assist individuals in recognizing and overcoming negative inclinations that manifest within their own beings. The methodology employed in this study is a literature review, specifically adopting a library research design. The primary sources of data for this research consist of reputable scholarly books and journals. The findings of this study reveal the pivotal role of intuition in the acquisition of knowledge, serving as a complementary faculty to rational and sensory capacities, thereby forming a comprehensive wellspring of human understanding. Through intuition, individuals possess an inherent ability to safeguard themselves from various perils, independent of conscious deliberation. The cultivation of a robust intuition can be achieved through the practice of Tazkiyatun Nafs, a process of self-purification aimed at alleviating the afflictions of the heart that contaminate the essence of the soul.